Enamel thickness per masticatory phases (ETMP): A new approach to assess the relationship between macrowear and enamel thickness in the human lower first molar. (May 2023) - Oxilia, Gregorio; Zaniboni, Mattia; Bortolini, Eugenio; Menghi Sartorio, Jessica C.; Bernardini, Federico; Tuniz, Claudio; Di Domenico, Giovanni; Pavičić, Dinko Tresić; Los, Dženi; Radović, Siniša; Balen, Jacqueline; Janković, Ivor; et al.
Abstract: Many anthropological studies have examined the functional implications of enamel thickness in human dental crowns. Despite limitations, Enamel thickness (ET) values are still used to infer taxonomic attribution in the genus Homo, and to identify mechanisms of functional adaptation against macrowear. However, only a few studies have tried to describe the possible relationship between ET and dental wear patterns in permanent lower first molars (M1 ) aiming to observe whether an adaptive response to the environmental and cultural context is detectable. The present work aims to investigate a possible signal of ET adaptive response in M1 (wear stage 3; Molnar, 1971) belonging to individuals who lived between the Neolithic (early 6th millennium BCE) and the Bronze Age (second half of the 2nd millennium BCE) in Croatia to identify any signal of change in dental tissue proportions based on archaeologically documented shifts in population structure and subsistence strategies. In order to do so, we explored 3D Average Enamel Thickness (AET) of the entire crown and wear pattern distribution among individuals and across chronological groups. We then described a new method called "Enamel Thickness per Masticatory Phases" (ETMP) involving the creation of virtual sections cutting enamel and coronal dentine in three parts based on masticatory phases, and explored the distribution of 3D AET accordingly. Finally, we performed geometric morphometric analysis on dental crown to ascertain possible morphological differences between Neolithic, Eneolithic, and Bronze Age groups. Results show that Bronze Age individuals differ from previous groups due to 1) higher values of ET in both the entire crown and specifically in the buccal area, 2) to an extensive wear pattern localized on the buccal side, and 3) to the distal extension of the hypoconid together with an extended mesio-distal shape of the crown. These patterns may represent an adaptive response of dental tissue to varying functional demands (e.g. archaeologically documented dietary shift). The study of ETMP therefore offers a more nuanced method, in addition to morphology and macrowear analysis, to document biocultural processes of change over time in archaeological populations through dental tissues. Highlights: New virtual method for the computation of 3D dental enamel thickness in humans is tested on Croatian individuals. Bronze Age individuals show the highest values of enamel thickness in both the dental crown and Buccal masticatory phase. Dental wear in Buccal masticatory phase discriminates Bronze Age individuals from individuals belonging to earlier groups. Dental crown shape morphology varies measurably across Neolithic, Eneolithic, and Bronze Age individuals of Croatia.